Cytoreductive surgery and post-operative heated pleural chemotherapy for the management of pleural surface malignancy. (November 2013) - Kodama, Ken; Higashiyama, Masahiko; Okami, Jiro; Tokunaga, Toshiteru; Fujiwara, Ayako; Imamura, Fumio; Nakayama, Tomio
Abstract Purpose: We retrospectively analysed the long-term outcomes of cytoreductive surgery and post-operative heated pleural chemotherapy (HPC) for thoracic malignancies with pleural spread. Materials and methods: Between 1987 and 2010, 160 patients were enrolled. There were 101 patients with non-small cell lung cancer (NSCLC), 25 with malignant pleural mesothelioma (MPM), 12 with thymoma, and 22 with tumours metastatic to the lung and pleura. Immediately after intra-thoracic administration of cisplatin or carboplatin, hyperthermia was performed by using an 8.00 MHz radiofrequency capacitive heating device for 1 to 4 courses in each patient. Results: There was no systemic toxicity or treatment-related mortality. Five-year overall survival rates were 37.4% in NSCLC, 15.9% in MPM, 91.7% in thymoma, and 25.8% in metastatic lung tumour. Five-year local relapse-free survival (RFS) rates were 55.2% in NSCLC, 24.4% in MPM, 64.8% in thymoma, and 27.2% in tumours metastatic to the lung and pleura. When 101 NSCLCs were categorised into pleural lavage cytology positive (grade 1: n = 37), limited extent of carcinomatous pleuritis (grade 2: n = 21), and extensive carcinomatous pleuritis (grade 3: n = 43), 5-year overall survival rates were 62.5%, 49.2%, and 13.6%, respectively. The local RFS was significantly better in group 1/2 than in group 3. Conclusions: Although our study has some of the usual weaknesses of a single institution retrospective study, cytoreductive surgery and HPC are feasible and safe. It is suggested that HPC may have a potential role for local control as adjuvant treatment for cytoreductive surgery in patients with minor pleural spread.